Canadian Consensus Recommendations for the Optimal Use of Enfuvirtide in HIV/AIDS Patients. Issue 3 (1st June 2006) - Rachlis, Anita; Angel, Jonathan; Harris, Marianne; Lalonde, Richard; Smaill, Fiona; Tremblay, Cecile; Tsoukas, Chris; Walmsley, Sharon
Abstract : BACKGROUND AND OBJECTIVES: An eight-member group consisting of Canadian infectious disease and immunology specialists and a family physician with significant experience in HIV management was convened to update existing recommendations, specifically intended for use by Canadian HIV-treating physicians, on the appropriate use of enfuvirtide in HIV/AIDS patients with resistance to other antiretroviral drugs. METHODS: Evidence from the literature and expert opinions of the group members formed the basis of the guidelines. Comments on the draft guidelines were obtained from other physicians across Canada with HIV expertise. The final guidelines represent the group's consensus agreement. RESULTS AND CONCLUSIONS: The recommendations were developed to guide physicians in optimal practices in patient selection for enfuvirtide treatment and subsequent patient management. The issues considered include positive predictors of response to enfuvirtide, stage of disease, optimization of the background regimen, early indicators of enfuvirtide response, and patient education and support.